Globalisation or regionalism? States, markets and the structure of international trade - Pelagidis, Theodore (2002)
Argues, on the basis of an analysis of the structure of international trade, that states remain a central factor, shaping the international economy. Opines that states that are weakest vis-à-vis society participate least in the international economy, while strong states that participate shape its structure on the basis of political as well as economic objectives.